Pendampingan Kurikulum Merdeka bagi Guru SD dan SMP di Negeri Sanahu, Kabupaten Seram Bagian Barat - Leasa, Marleny; Nuniary, Sefnath; Batlolona, John Rafafy; Suyanti, Marlen V. (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The Community Partnership Program (PKM) has the main objective of aiding the Independent Learning Curriculum at SD Negeri 122 Central Maluku and SMP Negeri 81 Central Maluku. This program is an effort to help schools recognize, understand, and develop the curriculum tools needed to implement the curriculum in 2023. Apart from that, it is also to produce Pancasila Student Profile products, as well as a literacy and numeracy environment in schools. This activity was motivated by the limitations of teachers and schools in recognizing the Independent Learning Curriculum which has only been implemented in the last 2 years. Therefore, teachers are still implementing the 2013 Curriculum. This activity also aims to introduce teachers to 21st century learning competencies in line with the demands of globalization, especially in various life skills. The partners who act as subjects in this activity are SD Negeri 122 Central Maluku and SMP Negeri 81 Central Maluku. Partners hope for changes in paradigms, plans and implementation of learning to recognize and develop learning tools for the Merdeka Belajar Curriculum. The activities carried out are: 1) introduction of the Independent Learning Curriculum, 2) Preparation of the Independent Learning Curriculum Toolkit, 3) Pancasila Student Profile, 4) Literacy and numeracy, 5) Training on developing learning evaluation instruments, 6) Learning practices. Through these various important activities, it is hoped that teachers will be able to recognize and develop learning tools in the Independent Learning Curriculum for implementation.